SHOSHANA ZUBOFF, The Age of Surveillance Capitalism: The Fight for a Human Future at the New Frontier of Power - Anderson, Jennifer (Archivaria, 2020)
The Age of Surveillance Capitalism: The Fight for a Human Future at the New Frontier of Power. Shoshana Zuboff. New York: Public Affairs, 2019. viii, 691 pp. ISBN 978-1-61039-569-4